Pergeseran Bahasa Jawa dalam Ranah Sosial Masyarakat Studi Kasus di Desa Petajen, Kecamatan Bajubang, Kabupaten Batang Hari - Baldi Arezky; Irma Suryani; Julisah Izar (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
This study raised the issue of the shift in the Javanese language that occurred in the social realm of the people in Petajen Village, Bajubang District, Batang Hari Regency. This study aims to look at the process of language shift from generation to generation as well as the factors that influence the occurrence of this shift process.The method in this study uses a qualitative approach with a descriptive type of research. The data in this research are in the form of fragments of conversation or spoken utterances from various events within the social realm of the Javanese ethical community in Petajen Village, Bajubang District, Batang Hari Regency. The data sources come from the first and second generations of Javanese ethnic families who live in Petajen Village. Data collection techniques used are observation, interviews, recording and note-taking techniques. The validation used is data trigulation technique.The results of this study obtained data in the form of fragments of oral conversations regarding how the language shift process in Petajen Village, Kec. Kab. Batangahari it happened. As an example of the data in the following quote